Distinctive Features of IR Spectra of Crude Oils of the Absheron Peninsula - Pashayev, A.M.; Valiyev, N.A.; Asgarov, K.A.; Musayev, A.A.; Mammadov, I.Kh.; Allahverdiyev, K.R.; Majidova, V.G. (Herald of Azerbaijan Engineering Academy, 2024)
Infrared (IR) spectroscopy provides useful information about hydrocarbon fluid inclusions in crude oils. In particular, the presence or absence of hydrocarbon functional groups may be qualitatively determined. It is known, there are 12 Oil-gas Production Companies (OGPC) in Azerbaijan, including 8 owned by Azerbaijan and 4 Joint Ventures. In most oil spills situations, it is desirable to have more than one analytical technique for detecting of spilled oil to its suspected source. In this paper we present first results of Fourier Transform IR (FTIR) spectroscopy spectra of crude oils taken from 6 OGPC of Azerbaijan Republic.